RHODODENDRON GUMINEENSE CRAVEN (ERICACEAE, SUBGENUS VIREYA), A NEW RECORD FOR INDONESIA - Yasper Michael Mambrasar (PTTI, 2018)
Yasper Michael Mambrasar. 2018. Rhododendron gumineense Craven (Ericaceae, Submarga Vireya), Rekaman Baru untuk Indonesia. Floribunda 6(1): 19–21. — Jumlah jenis Rhododendron di Indonesia dilaporkan sebanyak 229 jenis. Satu jenis Rhododendron dari Lembah Baliem, Indonesia yang sebelumnya diidentifikasi sebagai Rhododendron beyerinckianum Koord. telah diidentifikasi sebagai Rhododendron gumineense Craven, berdasarkan bentuk daun dan tangkai putik. Sehingga menambah jumlah jenis Rhododendron di Indonesia menjadi 230.Kata Kunci: Indonesia, Lembah Baliem, Rekaman baru, Rhododendron. Yasper Michael Mambrasar. 2018. Rhododendron gumineense Craven (Ericaceae, Subgenus Vireya), a new record for Indonesia. Floribunda 6(1): 19–21. — The number of Rhododendron species in Indonesia was reported as 229 species. A specimen of Rhododendron from the Baliem valley, Indonesia previously identified as Rhododendron beyerinckianum Koord. has been identified as Rhododendron gumineense Craven, based on leaf shape and style morphology. This increases the number of Rhododendrons in Indonesia to 230 species.Keywords: Indonesia, Baliem valley, New record, Rhododendron.